Performance characteristics of mode of ballast on energy efficiency indices of agricultural tyre in different terrain condition in controlled soil bin environment. (1st September 2019) - Kumar, Sanjeev; Noori, Md Tabish; Pandey, K.P.
Abstract: Efficient energy utilization of traction device includes maximization of energy efficiency indices (i.e. pulling ability and tractive power efficiency) with optimum slip range. The present study compares the performance of 13.6 × 28 bias and radial-ply tyres (T1 and T2) used in agricultural tractors under controlled soil bin conditions. With a view to reduce the wheel slippage, the test was conducted under varying mode of ballast loads using either iron or water including the base weight (1050 kg). The combination of load and inflation pressure was selected to achieve 20% deflection and performance test was conducted in soft (450 ± 50 kPa), medium (1150 ± 50 kPa) and hard soil (1750 ± 50 kPa) conditions. The average pulling ability and tractive power efficiency of the test tyres in case of iron ballast was found to be 2–7.5% and 0.5–8.89%, respectively, which was better than the corresponding liquid ballast. It was also observed that the maximum power output can be increased by the help of ballasting, the output power was found to be more in case of corresponding weight of 50 and 75% equivalent weight of iron ballast compared to liquid ballast. Highlights: Modes of ballast load on Energy efficiency indices were analysed. Instrumentation was done for measurement of energy efficiency parameters. Performance comparison of iron ballast compared to liquid ballast. Iron ballast load was found to be better than equivalent weight of liquid ballast.